World EnergyTransitions Outlook 2024: 1.5 C Pathway. - Al-Zoghoul, Sonia; Collier, Ute; Gafaro, Francisco; Guinto, Hannah Sofía; Hawila, Diala; Hussain, Bilal; Jacob, Ines; Janeiro, Luis; Var der Lugt, Iris; Nsengiyaremye, Jerome; Pinheiro Pupo Nogueira, Larissa; Jiménez-Navarro, Juan-Pablo; et al. (International Renewable Energy Agency, 2024)
IRENA’s 1.5°C Scenario, set out in the World Energy Transitions Outlook, presents a pathway to achieve the 1.5°C target by 2050, positioning electrification and efficiency as key transition drivers, enabled by renewable energy, clean hydrogen and sustainable biomass.
Keywords: Recursos energéticos renovables; Energía eléctrica; Transición energética; Calentamiento global; IRENA; World energy outlook; Electrification; Efficiency; World energy transitions outlook; Renewable energy